A cross sectional study on factors influencing non-adherence to treatment among paediatric tuberculosis patients in field practice area of Osmania Medical College, Hyderabad - Panuganti, Sreelatha; Bhavani, Kenche; Vijayasree, L.; Krishna, Ananda (International Journal Of Community Medicine And Public Health, 2022)
Background: Tuberculosis (TB) remains to be a major burden in India. Treatment adherence is a key factor in the outcome of therapy. Non-adherence may also result in acquired drug resistance. This study has been one of the very few research endeavours to identify factors associated with non-adherence to TB treatment among paediatric patients in Hyderabad. The objectives are to determine the factors influencing non-adherence to treatment among paediatric TB patients and to study the role of sociodemographic factors in non-adherence to treatment. Methods: A cross sectional study was conducted between June 2021 to September 2021 among paediatric TB patients ≤18 years old who were on anti-TB treatment in field practice area of Osmania Medical College, Hyderabad. By using convenient sampling method, a sample size of 150 has been taken. Data was collected using a pretested semi structured questionnaire. Data was entered into Microsoft excel and analysed using Epi Info version 7.2.2.6 and frequencies, proportions, and Chi square tests used. Results: Among the 150 paediatric TB patients, majority 56.2% of the patients belong to male gender. Non-adherent to anti-tuberculosis treatment were 18%. In this, 10% belongs to younger age (<5 years), 4% females, 14% males, 13.3% rural residence, 4.7% urban residency, 14% were having side effects. The presence of side effects to anti-tubercular is the main influencing factors for non-adherence to treatment. Conclusions: The identification of various factors could help in increasing the knowledge about TB and in taking measures to cope-up with side effects to anti-tubercular medications which is required to improve treatment adherence.